Extended, virtual and augmented reality in thoracic surgery: a systematic review. (20th September 2021) - Arjomandi Rad, Arian; Vardanyan, Robert; Thavarajasingam, Santhosh G; Zubarevich, Alina; Van den Eynde, Jef; Sá, Michel Pompeu B O; Zhigalov, Konstantin; Sardiari Nia, Peyman; Ruhparwar, Arjang; Weymann, Alexander
Abstract: : OBJECTIVES: Extended reality (XR), encompassing both virtual reality (VR) and augmented reality, allows the user to interact with a computer-generated environment based on reality. In essence, the immersive nature of VR and augmented reality technology has been warmly welcomed in all aspects of medicine, gradually becoming increasingly feasible to incorporate into everyday practice. In recent years, XR has become increasingly adopted in thoracic surgery, although the extent of its applications is unclear. Here, we aim to review the current applications of XR in thoracic surgery. METHODS: A systematic database search was conducted of original articles that explored the use of VR and/or augmented reality in thoracic surgery in EMBASE, MEDLINE, Cochrane database and Google Scholar, from inception to December 2020. RESULTS: Our search yielded 1494 citations, of which 21 studies published from 2007 to 2019 were included in this review. Three main areas were identified: (i) the application of XR in thoracic surgery training; (ii) preoperative planning of thoracic procedures; and (iii) intraoperative assistance. Overall, XR could produce progression along the learning curve, enabling trainees to reach acceptable standards before performing in the operating theatre. Preoperatively, through the generation of 3D-renderings of the thoracic cavity and lung anatomy, VR increases procedural accuracy and surgical confidence through familiarization of the patient's anatomy. XR-assisted surgery may have therapeutic use particularly for complex cases, where conventional methods would yield inadequate outcomes due to inferior accuracy. CONCLUSION: XR represents a salient step towards improving thoracic surgical training, as well as enhancing preoperative planning and intraoperative guidance. Abstract : Extended reality (XR), encompassing both virtual (VR) and augmented reality (AR), allows the user to interact with a computer-generated environment based on reality.